168 AN EXPLORATION OF ATRIAL FIBRILLATION AND ANTICOAGULATION IN STROKE PATIENTS WHO UNDERGO THROMBECTOMY IN A TERTIARY THROMBECTOMY CENTRE. (25th October 2022) - Murphy, J; Kelly, R; Cathasaigh, CN; Murphy, D; Cloney, T; Hayes, K; Arrigan, G; O'Sullivan, A; Barry, P; James, K; Healy, L
Abstract: Background: Atrial Fibrillation is a significant cause of ischaemic stroke. Prevalence of atrial fibrillation in patients requiring thrombectomy is approximately 33%. Embolic thrombi which develop due to Atrial fibrillation may become targets for clot removal by thrombectomy in appropriate patients. Anticoagulation is one of the mainstays of treatment for atrial fibrillation. Methods: A list of patients who had thrombectomy performed for ischaemic stroke in 2021 was compiled. Charts were reviewed to establish the prevalence of atrial fibrillation and the rates of appropriate dosing of anticoagulant. Of those who were not anticoagulated, we aimed to establish if there was a clear reason for this. This was performed in a tertiary referral centre with 24/7 access to thrombectomy. Results: 97 patients had thrombectomy performed for ischaemic stroke in 2021. 34/97(35%) had atrial fibrillation (21/97 pre-existing, 13/97 newly diagnosed on admission). 15/21 were anticoagulated and 6/21 were not anticoagulated at the time of their stroke. 5/6 had a clear reason documented for stopping anticoagulation. One patient had stopped anticoagulation due to cost. Of those with atrial fibrillation who were anticoagulated at the time of their stroke, 11 were anticoagulated with a Direct-Acting AntiCoagulant (DOAC) and four were anticoagulated with Warfarin. Of the Warfarin group, just one patients' INR was therapeutic at the time of their stroke. Of the DOAC group, all were on the appropriate dose. Conclusion: Stroke patients requiring thrombectomy are a group who may suffer the largest strokes. Incidence of atrial fibrillation was similar to previous studies. It was encouraging that there was a documented reason for all patients who were not anticoagulated, and that the DOAC dose was appropriate. Issues with therapeutic levels of Warfarin are further highlighted here. This study concludes that we may not be as bad at anticoagulation as we may think.